2010
DOI: 10.1080/09658211003762092
|View full text |Cite
|
Sign up to set email alerts
|

Short-term memory for emotional faces in dysphoria

Abstract: The study aimed to determine if the memory bias for negative faces previously demonstrated in depression and dysphoria generalises from long- to short-term memory. A total of 29 dysphoric (DP) and 22 non-dysphoric (ND) participants were presented with a series of faces and asked to identify the emotion portrayed (happiness, sadness, anger, or neutral affect). Following a delay, four faces were presented (the original plus three distractors) and participants were asked to identify the target face. Half of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
1
9
1
Order By: Relevance
“…The prediction that dysphoric participants would exhibit poorer working memory (lower OSPAN scores) in comparison to the non-dysphoric group was not supported by our data. This is not consistent with the findings of previous studies (Christopher & McDonalds, 2005;Hubbard et al, 2016, Joormann & Gotlib, 2008Noreen & Ridout, 2010;Rose & Ebmeier 2006). One possible explanation concerns the participant sample used in the different studies.…”
Section: Discussioncontrasting
confidence: 97%
“…The prediction that dysphoric participants would exhibit poorer working memory (lower OSPAN scores) in comparison to the non-dysphoric group was not supported by our data. This is not consistent with the findings of previous studies (Christopher & McDonalds, 2005;Hubbard et al, 2016, Joormann & Gotlib, 2008Noreen & Ridout, 2010;Rose & Ebmeier 2006). One possible explanation concerns the participant sample used in the different studies.…”
Section: Discussioncontrasting
confidence: 97%
“…The absence of a clear sad benefit in dysphoria in other previous work (Noreen and Ridout, 2010) may be explained by the characteristics of the sample of that study, which included only healthy individuals who scored high on a depression scale. Deveney and Deldin (2004) did investigate patients with Major Depressive Disorder (MDD) and did not find a bias for sad faces in working memory, but they used a load of only one face.…”
Section: Introductionmentioning
confidence: 76%
“…We showed that individuals high in negative cognitive style, when distressed, show a bias towards the negative self-face (with respect to the negative nonself face), even within brief short-term memory episodes. Conversely, we found no evidence of a ''sad benefit'' during WM processing (see also Noreen & Ridout, 2010).…”
Section: Discussionmentioning
confidence: 40%
“…A long-term memory bias for sad faces has been found in patients with depression (Gilboa-Schechtman, Erhard-Weiss, & Jeczemien, 2002;Ridout, Astell, Reid, Glen, & O'Carroll, 2003), in individuals experiencing dysphoria (Jermann et al, 2008;Ridout, Noreen, & Johal, 2009), and in individuals in an induced sad mood (Ridout, Dritschel, et al, 2009). A short-term memory bias for sad faces has been found in patients with melancholic depression (Linden, Jackson, Subramanian, Healy, & Linden, 2011), but not in individuals with subclinical dysphoria (Noreen & Ridout, 2010). The results of these studies show abnormal recognition memory for faces displaying sadness in depressed and depression-susceptible groups, or after an experimentally induced sad mood.…”
Section: Discussionmentioning
confidence: 97%